Оптимальные решения многокритериальных комбинаторных задач на размещениях - Колечкина, Л.Н. (Теорія оптимальних рішень, 2007)
The problem of multicriterion combinatorial optimization on placing is examined. It is grounded, that the effective decisions of task are in the tops of polyhedron of placing. The algorithm of finding of Pareto-optimum estimations is represented for combinatorial multicriterion problems.